Epidemiological analysis of COVID-19 cases in the brazilian prison context (Research, Society and Development, 2020)
Objective: to analyze the epidemiological surveillance of cases of SARS-CoV-2 infection in the Brazilian prison context. Methodology: Cross-sectional study, with data from weekly COVID-19 case records in Brazilian penitentiaries, from the online website of the National Penitentiary Department (DEPEN) and epidemiological bulletins provided by the Coordination for the Execution of Prison Health in Ceará (CESAP), referring to the months of March to August 2020. Results: the Southeast region concentrates the largest number of suspected and confirmed cases of COVID-19 in penitentiaries, with the state of São Paulo accumulating 74.6% (n = 4553) of confirmed cases. The South region is the smallest among the other Brazilian regions, with 307 cases; and, among these, 73.7% (n = 264) are concentrated in the state of Rio Grande do Sul (RS). Conclusion: although the spread of the Sars-CoV-2 virus in Brazilian prisons has affected prisoners and workers in these units, it is still a smaller percentage in relation to the Brazilian population in general and with a lower mortality rate than countries considered developed.